2016
DOI: 10.1521/soco.2016.34.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Social Belonging Motivates Categorization of Racially Ambiguous Faces

Abstract: Categorizing racially ambiguous individuals is multifaceted, and the current work proposes social-motivational factors also exert considerable influence on how racial ambiguity is perceived, directing the resolution of ambiguity in a manner that is functionally beneficial to the perceiver. Four studies tested two motivations related to social belonging: belonging needs and racial identification. Greater need to belong and racial identification (Study 1), and two types of social belonging threats-social exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 55 publications
2
51
0
1
Order By: Relevance
“…Another potential gateway group are individuals with mixed ethnic or racial parentage. Although they are a fast‐growing part of the population in many globalized societies—in England and Wales, for example, the number of people identifying as multiethnic has almost doubled between 2001 and 2011 (Jivraj, )—research continues to focus on how multiracials identify and how they are perceived by monoracial majority and minority group members (Gaither, Pauker, Slepian, & Sommers, ), but rarely on how they could affect relations between majority and minority monoracial communities.…”
Section: Empirical Evidence For the Potential Of Gateway Groupsmentioning
confidence: 99%
“…Another potential gateway group are individuals with mixed ethnic or racial parentage. Although they are a fast‐growing part of the population in many globalized societies—in England and Wales, for example, the number of people identifying as multiethnic has almost doubled between 2001 and 2011 (Jivraj, )—research continues to focus on how multiracials identify and how they are perceived by monoracial majority and minority group members (Gaither, Pauker, Slepian, & Sommers, ), but rarely on how they could affect relations between majority and minority monoracial communities.…”
Section: Empirical Evidence For the Potential Of Gateway Groupsmentioning
confidence: 99%
“…With respect to perceivers, research has yet to focus on how non‐White individuals perceive multiracials (see Chen et al, in press; Chen & Ratliff, ; Gaither, Pauker, Slepian, & Sommers, ; Ho et al, ; Pauker & Ambady, , for a few exceptions). Yet research on non‐White perceivers has generated novel insights, such as Black Americans' perception of linked fate with Black‐White biracials (Ho et al, ) and Asian Americans' rejection of Asian‐White biracials because they are skeptical of biracials' allegiances (Chen et al, in press).…”
Section: Limitations Of the Existing Literaturementioning
confidence: 99%
“…Hypodescent served as a legal mechanism to deny part-Black multiracial persons the rights and privileges that were exclusively afforded to monoracial Whites (see Davis, 1991). Many recent studies have shown that perceivers engage in hypodescent when categorizing Black-White multiracial individuals in that they categorize them as Black more often than as White (Cooley, Brown-Iannuzzi, Brown, & Polikoff, 2017;Freeman, Pauker, & Sanchez, 2016;Gaither, Pauker, Slepian, & Sommers, 2016;Ho, Sidanius, Levin, & Banaji, 2011;Ho, Sidanius, Cuddy, & Banaji, 2013;Krosch & Amodio, 2014;Krosch, Bernsen, Amodio, Jost, & Van Bavel, 2013;Peery & Bodenhausen, 2008, Experiment 1;. Thus, from the existing social psychological literature, one could conclude that multiracial individuals are categorized according to the rule of hypodescent.…”
mentioning
confidence: 99%